ANALISIS GERAK ROBOT LINE TRACER DENGAN PROGRAM ARTIFICIAL INTELLEGENCE MENGGUNAKAN MICROCONTROLLER AT89S51 - Widhiada, I Wayan (Jurnal Energi Dan Manufaktur; Vol 2, No.2 Desember 2007)
The research discussed about the work system of The Line Tracer Robot movement analysis, with using the AI program and assembler programming language. The tools that used are microcontroller type AT89S51, Meitan ASM 2005 Standard Edition version 1.00 as development tools and Meitan 2005 as the hardware tools modul. From the result of research, it can be known that The Line Tracer Robot with AI program is able to show differences, among the white as a based colour and black as a line colour. The AI program is able to accelerate/coordinate the system of work, between the censor and the parts of driver motor combinations. The robot that did not use AI program can not run well, and the wheel just able to rotate in one direction.
Keywords: Line tracer robot, Artificial Intelligence programming, AT89S51 MCU type